ANALISA FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PAKAIAN SYAR’I DI TOKO KHADIJAH BALIKPAPAN: Mardiyanah, Rahajeng Cahyaning Putri Cipto - Rahajeng Cahyaning Putri Cipto., SE., M.EK (STIE Madani Balikpapan, 2022)
This research was conducted at the Khadijah Balikpapan store. This study aims to determine or analyze the variables of cultural factors, social factors, personal factors, and psychological factors on consumer purchasing decisions at the Khadijah Balikpapan Store. Data collection methods through questionnaires. The population in this study are all consumers who shop at Khadijah Balikpapan. The sampling technique uses saturated sampling. The number of samples used was 103 respondents. This type of research is quantitative. The research method is by distributing questionnaires with a Likert scale model, which is analyzed using the classic assumption test and multiple linear regression with SPSS version 20 statistical tools. The results of this study indicate that the variables of cultural factors and psychological factors partially have a significant effect on consumer purchasing decisions at Balikpapan Khadijah Stores, while social factors and personal factors do not partially influence purchasing decisions at Khadijah Balikpapan Stores. And psychological variables are the most dominant variables influencing purchase decisions at the Khadijah Balikpapan Store